Earning Per Share, Dividend Per Share dan Harga Saham Perusahaan Batu Bara - Pratiwi, Ni Luh Mega; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2023)
This study aims to provide empirical evidence on the effect of earnings per share and dividend per share on stock prices. This research was conducted at coal issuers listed on the Indonesia Stock Exchange (IDX). A total of 36 samples were taken, using a non-probability sampling technique using a purposive sampling technique. Data was collected using non-participant observation. The analysis technique used is multiple linear analysis techniques. The results of the study stated that earnings per share and dividend per share had a positive effect on the share prices of coal issuers listed on the IDX for the 2018-2020 period. Keywords: Stock Price; Earning Per Share; Dividend Per Share; Coal Company